On Some Fractional Magnetic Problems - Frédéric D. Y. Zongo; Salifou Korbeogo; Arouna Ouédraogo (Pan-American Journal of Mathematics)
In this article, we study existence of weak solutions and the unique continuation property of the nonlocal fractional magnetic equation. First, we use a variational technique to prove existence of weak solutions for the fractional Schrödinger equation with magnetic field. Moreover, we show the doubling property main argument to unique continuation property via Carleman estimates.